Developing an ex-vivo model to investigate chorionic villus sampling technique. (18th April 2012) - Skorupskaite, K; Walker, J; Stock, S
Abstract : Introduction: There is little consensus regarding the optimal technique for transabdominal chorionic villus sampling (CVS) and the number of times that the sampling needle is advanced and withdrawn whilst within the placenta varies between the operators. We designed a model to investigate differences in CVS technique, and used it to investigate the effect of needle movement on the quantity of aspirated chorionic villi. Methods: Ethical approval was obtained. Placentae from medical termination of pregnancy (n=8; 11-19 weeks gestation) were supported vertically between two sheets of polypropylene, marked at 0.5cm intervals. An 18-gauge needle was advanced and withdrawn one, five or ten times, determined by selection of numbers from an opaque container. Villi were wet-weighed, by an operator blind to the number of 'passes' by which the specimen was obtained. Each number of 'passes' was tested 26 times. Data was analysed using one-way ANOVA. Results: The mean weight of chorionic villi obtained after five 'passes' was significantly higher than that obtained after one pass (61.27 mg [SD 26.74] with five 'passes' versus 40.17 mg [SD 21.75] with one 'pass'; p<0.05) but no different from the sample obtained after ten 'passes' (66.45 mg [SD 35.71]; p>0.05). Conclusions: We have developed a model which can be used to investigate differences in CVS technique, and shown that the number of times the needle is advanced and withdrawn within the placenta affects the amount of villi obtained. Further work will focus on determining the optimal techniques to obtain sufficient villi, whilst minimising tissue damage.